2011
DOI: 10.4067/s0718-58392011000400005
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene, Enzymatic and Respiratory Pattern Evolution in Loquat (Eriobotrya japonica (Thunb.) Lindl.) cv. Golden Nugget in the Last four Sequential Stages of Maturation

Abstract: There is some controversy regarding the respiratory pattern of loquat (Eriobotrya japonica [Thunb.] Lindl.). Thus in order to provide information on this aspect of loquat, fruit of 50-70 g, from cv. Golden Nugget were harvested in four stages of maturity: green (BBCH 709), color break (BBCH 801), yellow (BBCH 807), and orange (BBCH 809). The parameters evaluated in each stage were: soluble solids, titratable acidity, respiration, ethylene generation, and activity of the enzymes pectin methyl esterase (PME), pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…As increasing the fruit maturity stage, the SSC also increases, but the TA decreases. It might be due to the conversion of acid to sugar (gluconeogenesis) (Undurraga et al, 2011;Zhao et al, 2021). Additionally, the SSC of abiu fruit on each maturity stage increased, and the TA content decreased throughout the storage period.…”
Section: Discussionmentioning
confidence: 99%
“…As increasing the fruit maturity stage, the SSC also increases, but the TA decreases. It might be due to the conversion of acid to sugar (gluconeogenesis) (Undurraga et al, 2011;Zhao et al, 2021). Additionally, the SSC of abiu fruit on each maturity stage increased, and the TA content decreased throughout the storage period.…”
Section: Discussionmentioning
confidence: 99%
“…In fruit of several loquat cultivars a climacteric-like increase in ethylene production and respiration rate are coincident with the change in peel colour, suggesting a climacteric ripening pattern (Hamauzu et al, 1997;Amoros et al, 2003;Jiang et al, 2011). Other authors only reported increases in ethylene production but not in the respiration rate (Undurraga et al, 2011). In a recent study, we found a significant increment in ethylene production in on-tree fruit but the application of the ethylene-releasing compound, ethephon, did not induce an autocatalytic enhancement of the ethylene production rate.…”
Section: Introductionmentioning
confidence: 93%
“…Lindl.) is a subtropical evergreen fruit tree belonging to the family Rosaceae, specifically the subfamily Pomoideae, native to southeast China (Undurraga et al., 2011 ). It is characterized by a rich source of phenolics and carotenoids (Li, Xu, & Chen, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lindl.) is a subtropical evergreen fruit tree belonging to the family Rosaceae, specifically the subfamily Pomoideae, native to southeast China (Undurraga et al, 2011).It is characterized by a rich source of phenolics and carotenoids (Li, Xu, & Chen, 2016). Furthermore, cough and reducing phlegm which is particularly significant, so it is deeply loved for its dual-purpose medicine and food (Huang et al, 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation